Additional Value of CH4 Measurement in a Combined 13C/H2 Lactose Malabsorption Breath Test: A Retrospective Analysis - Els Houben (Nutrients, 2015)
The lactose hydrogen breath test is a commonly used, non-invasive method for the detection of lactose malabsorption and is based on an abnormal increase in breath hydrogen (H2) excretion after an oral dose of lactose. We use a combined 13C/H2 lactose breath test that measures breath 13CO2 as a measure of lactose digestion in addition to H2 and that has a better sensitivity and specificity than the standard test. The present retrospective study evaluated the results of 1051 13C/H2 lactose breath tests to assess the impact on the diagnostic accuracy of measuring breath CH4 in addition to H2 and 13CO2. Based on the 13C/H2 breath test, 314 patients were diagnosed with lactase deficiency, 138 with lactose malabsorption or small bowel bacterial overgrowth (SIBO), and 599 with normal lactose digestion. Additional measurement of CH4 further improved the accuracy of the test as 16% subjects with normal lactose digestion and no H2-excretion were found to excrete CH4. These subjects should have been classified as subjects with lactose malabsorption or SIBO. In conclusion, measuring CH4-concentrations has an added value to the 13C/H2 breath test to identify methanogenic subjects with lactose malabsorption or SIBO.